Desperate Times Call for Desperate Measures: Bridging to Transplant in the Face of Central Device Infection. Issue 4 (30th March 2023) - Jenkins, Haley; Starling, Randall C.; Soltesz, Edward G.; Tong, Michael Z.Y.; Weiss, Aaron J.
Abstract : Patients with durable left ventricular assist devices (LVAD) that develop central device infections can prove prohibitively challenging to treat and may require device explant for source control. In bridge to transplant (BTT) LVAD patients, the management of mediastinal infection is further complicated by changes in the 2018 United Network of Organ Sharing (UNOS) allocation system, which resulted in a comparatively lower listing status than in its previous iteration. We present the case of a 36-year-old male with nonischemic cardiomyopathy status post Heartmate 3 (HM3) implantation as BTT who after a year of stable HM3 support, developed a severe bacterial infection along the outflow graft. Despite attempts at finding a suitable donor at his current listing, his clinical status continued to deteriorate. To obtain infection source control, he underwent LVAD explant and insertion of a left axillary artery Impella 5.5 ventricular assist device for necessary hemodynamic support. The patient's listing was upgraded to Status 2, and following the identification of a suitable donor, underwent successful heart transplantation. This case highlights the limitation of the updated UNOS heart allocation system for patients with central device infections and describes the successful use of salvage temporary mechanical circulatory support to bridge to transplantation.